Comparison in Some Biochemical and Hematological Tests Between Chronic Hepatitis B and C - Hussein, R.H. (Ibn AL-Haitham Journal For Pure and Applied Sciences, 2016)
Chronic viral hepatitis is an important health problem in the world, where hepatitis B virus (HBV) or hepatitis C virus (HCV) infections are the main causes of liver insufficiency. The study included 100 blood samples from patients with chronic viral hepatitis, fifty of them with HBV infection and 50 with HCV infection. Twenty apparently healthy age and gender matched subjects were included as a control group. Out of the 50 patients with HBV, 36(72%) were males and 14(28%) were females. Thirty two (64%) patients with HCV were males and 18(36%) were females. The mean age for HBV patients was 36.9 ± 15.8 year and for HCV patients it was 39.9 ±14.2 year. The results of the liver function tests showed no significant difference between HBV and HCV patients. Both of HBV and HCV patients showed a significant difference regarding liver function tests when compared with the control group. Total white blood cell count and hemoglobin concentration were lower (4296± 1050.9 cell/ mm3 and 10.9 ± 2.2g/dl respectively) in HCV patients than those in HBV patients (6224 ± 1749.1 cell /mm3 and 13.4 ±1.3 g/dl ) with a significant difference. However there was no significant difference between HBV patients and control regarding total white blood cell count and hemoglobin concentration. Aim of study: to compare between chronic hepatitis B, chronic hepatitis C and control regarding some hematological and biochemical parameters.